Asymptomatic Moyamoya Disease: Literature Review and Ongoing AMORE Study - Group, AMORE Study; KURODA, Satoshi (Neurologia medico-chirurgica, 2015)
Recent development of a non-invasive magnetic resonance examination has increased the opportunity to identify asymptomatic patients with moyamoya disease who have experienced no cerebrovascular events. However, their clinical features, prognosis, and treatment strategy are still unclear because of small number of subjects and short follow-up periods. Therefore, we have designed Asymptomatic Moyamoya Registry (AMORE) study in Japan. The objectives of this nation-wide, multi-center prospective study are to clarify long-term prognosis of asymptomatic patients with moyamoya disease and to determine the risk factors that cause ischemic and hemorrhagic stroke in them. In this article, we review the published data on asymptomatic moyamoya disease and report the on-going multi-center prospective cohort study, AMORE study. We would like to emphasize the importance to determine the clinical features, prognosis, and treatment strategies of asymptomatic moyamoya disease in very near future.